2017
DOI: 10.1051/matecconf/201710901004
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Resistance Property of a Zn-AI-Mg Alloy with Different Solidification Processes

Abstract: Zn-Al-Mg alloy coating attracted much attention due to its high corrosion resistance properties, especially high anti-corrosion performance at the cut edge. As the Zn-Al-Mg alloy coating was usually produced by hot-dip galvanizing method, solidification process was considered to influence its microstructure and corrosion properties. In this work, a Zn-Al-Mg cast alloy was melted and cooled to room temperature with different solidification processes, including water quench, air cooling and furnace cooling. Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results showed that by increasing the solidification rate, more aluminum remained in the primary crystals. Electrochemical analysis indicated that with a decreasing solidification rate, the corrosion current density of the Zn-Al-Mg alloy decreased, indicating higher corrosion resistance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that by increasing the solidification rate, more aluminum remained in the primary crystals. Electrochemical analysis indicated that with a decreasing solidification rate, the corrosion current density of the Zn-Al-Mg alloy decreased, indicating higher corrosion resistance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%